2020
DOI: 10.1038/s41598-020-77046-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting stability of plasma brain-derived neurotrophic factor

Abstract: Circulating concentrations of brain-derived neurotrophic factor (BDNF) have been linked to cancer, neuropsychiatric, diabetes, and gynecological disorders. However, factors influencing plasma storage and subsequent BDNF quantification are incompletely understood. Therefore, the anticoagulant used in plasma separator tubes, storage-time, storage-temperature, and repeated freeze–thaw cycles on circulating BDNF concentrations was evaluated. Peripheral blood samples were collected from healthy women (n = 14) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although our study validates altered expression in the depressed patient, we also discovered a significant amount of heterogeneity between studies, significantly influencing the BDNF expression in drug‐naïve or drug‐free depressed patients. We speculate that a high heterogeneity might have resulted from between‐sample characteristics, such as alcohol consumption and cigarette smoking, sleep‐related issue, circadian variation, socioeconomic status, and differences in the severity of patient samples’ clinical features such as a history of depression (Bus et al., 2012 ; Miranda et al., 2019 ; Wessels et al., 2020 ). These heterogeneous variables are interdependent in a complex manner, and any disruption of this complex mechanism may give rise to depression (Athira et al., 2020 ; Beirão et al., 2020 ; McEwen & Akil, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study validates altered expression in the depressed patient, we also discovered a significant amount of heterogeneity between studies, significantly influencing the BDNF expression in drug‐naïve or drug‐free depressed patients. We speculate that a high heterogeneity might have resulted from between‐sample characteristics, such as alcohol consumption and cigarette smoking, sleep‐related issue, circadian variation, socioeconomic status, and differences in the severity of patient samples’ clinical features such as a history of depression (Bus et al., 2012 ; Miranda et al., 2019 ; Wessels et al., 2020 ). These heterogeneous variables are interdependent in a complex manner, and any disruption of this complex mechanism may give rise to depression (Athira et al., 2020 ; Beirão et al., 2020 ; McEwen & Akil, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF concentrations in plasma are much lower than in serum, while serum BDNF is more stable, its amount is modified by temperature and time of clotting [ 36 ] Plasma BDNF is influenced by several clinical factors, such as, inter alia, body weight [ 37 ] and circadian rhythm [ 35 ] and is sensitive to preparation procedure [ 38 40 ]. We can only speculate that AF-BDNF acts like human plasma BDNF and we did not find differences between group A and group B apart from maternal pre-pregnancy BMI.…”
Section: Discussionmentioning
confidence: 99%
“…(2014), where BDNF measured in serum increased during the first hour of coagulation at 25°C and were relatively stable with a clotting time between one and 48 h. In contrast, a study by Amadio and colleagues (2017), demonstrated that serum BDNF samples incubated at 37°C, reached a plateau after 30 min, whereas 120 min were necessary to obtain similar BDNF levels at room temperature. Furthermore, Wessels and colleagues (2020) noted that the type of plasma separator tube, storage duration, and number of freeze–thaw cycles can impact the quantification of plasma BDNF concentration. In addition, plasma stored at −80°C compared to −20°C tends to have less variability in mean BDNF concentrations.…”
Section: Measurement Of Bdnfmentioning
confidence: 99%